2019
DOI: 10.1002/term.2870
|View full text |Cite
|
Sign up to set email alerts
|

A new possibility in fertility preservation: The artificial ovary

Abstract: Conventional fertility preservation methods such as oocyte or embryo cryopreservation are currently insufficient to treat including those patients with prepubertal cancer and premature ovarian failure. Ovarian tissue cryopreservation presents as an alternative but has limitations with a potential risk of reintroducing malignant cells in patients who recover from cancer, those of chemotherapy prior to tissue cryopreservation. The so called “artificial ovary” aims to resolve this issue by transplanting isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 189 publications
(261 reference statements)
0
25
0
Order By: Relevance
“…in humans. Research is underway in the field of reproductive medicine using bioprinting technologies, in particular, the biofabrication of artificial ovaries[ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…in humans. Research is underway in the field of reproductive medicine using bioprinting technologies, in particular, the biofabrication of artificial ovaries[ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the technique may be used to develop follicles under in vitro conditions, thereby avoiding tumor contamination or placing these isolated follicles in the transplantation area with the assistance of scaffolds. An artificial ovary can be used to mature oocytes through a multistep process, including sequential in vitro culturing of oocytes, isolated follicles, and OT [136][137][138][139][140][141][142][143][144][145]. Multiple studies have shown that the live birth rate using this option is comparable to that of conventional IVF [146,147].…”
Section: Artificial Ovariesmentioning
confidence: 99%
“…To date, animal studies have demonstrated that this approach restores endocrine function, also enabling in vivo follicular development and successful pregnancy; however, no successful human trials have been reported [138][139][140]142]. Developing techniques through which to increase follicular recovery rate and optimize scaffold design, as well as transplantation techniques to prevent postoperative ischemia, and genetic safety considerations, are all necessary for safer and more consistent human clinical applications [136].…”
Section: Artificial Ovariesmentioning
confidence: 99%
“…There is an accumulating evidence of utility success of ovarian auto graft to prevent or postpone the premature ovarian failure [28]. The implanted ovarian tissue called artificial ovary could restore the endocrine function and the ability to get successful pregnancy [29].…”
Section: Ovarian Auto-graftingmentioning
confidence: 99%